UPAYA PENINGKATAN KEMAMPUAN KOMUNIKASI SISWA DALAM PEMBELAJARAN IPS MELALUI MODEL PROBLEM-BASED LEARNING - Ni Komang Pande Tri Rahayu; I Nyoman Laba Jayanta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Communication skills are an essential competency in Social Studies learning; however, in practice, students’ communication skills are still relatively low. Therefore, a learning model that encourages active student participation is needed, one of which is Problem Based Learning (PBL). This study aims to analyze the improvement of students’ communication skills in Social Studies learning through the implementation of the PBL model. The research method used is qualitative research with a literature review approach by examining various relevant sources, including books and journal articles. The results of the review indicate that the implementation of the Problem Based Learning model can improve students’ communication skills through discussion activities, group work, and problem-solving. In addition, the PBL model creates Social Studies learning that is more interactive, participatory, and meaningful. Thus, the Problem Based Learning model can be used as an effective alternative to improve students’ communication skills.